1983
DOI: 10.1111/j.1432-1033.1983.tb07360.x
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Phosphatases Invloved in Cellular Regulation. 4. Classification of Two Homogeneous Myosin Light Chain Phosphatases from Smoth Muscle as Protein Phosphatase-2A1 and 2C, and a Homogeneous Protein Phosphatase from Reticulocytes Active on Protein Synthesis Initiation Factor eIF-2 as Protein Phosphatase-2A2

Abstract: Two homogeneous protein phosphatases, termed ‘smooth muscle phosphatase‐I’ and ‘smooth muscle phosphatase‐III’, isolated from turkey gizzard as enzymes active against the 20‐kDa light chain of smooth muscle myosin, and a third homogeneous protein phosphatase from rabbit reticulocytes, purfied as an enzyme active against protein synthesis initiation factor eIF‐2, were classified using the criteria defined by Ingebritsen and Cohen [Eur J. Biochem. (1983) 132, 255–261]. All three enzymes were type‐2 protein phops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…PP2A and PP1c both dephosphorylate isolated RLC, but not RLC bound to myosin heavy chain as in smooth muscle heavy meromyosin (Pato et al . ). It is noteworthy that there was significant MLCP activity with smooth muscle heavy meromyosin without MYPT1 in a soluble cytosolic fraction containing PP1cδ from wild‐type tissues, in addition to the significant phosphatase activity in MYPT1‐deficient tissues.…”
Section: Discussionmentioning
confidence: 97%
“…PP2A and PP1c both dephosphorylate isolated RLC, but not RLC bound to myosin heavy chain as in smooth muscle heavy meromyosin (Pato et al . ). It is noteworthy that there was significant MLCP activity with smooth muscle heavy meromyosin without MYPT1 in a soluble cytosolic fraction containing PP1cδ from wild‐type tissues, in addition to the significant phosphatase activity in MYPT1‐deficient tissues.…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that both glycogen synthase and eIF-2 can be phosphorylated by protein kinases from rabbit reticulocytes and rabbit muscle that are similar, if not identical, enzymes (DePaoli-Roach et al, 1981). Similarly, although the physiological specificities of particular phosphatases remain to be fully evaluated, it is evident that only a few enzymes can account for the known dephosphorylation activities involved in the regulation of glycogen metabolism, protein synthesis, and other cellular processes (Ingebritsen and Pato et al, 1983;Foulkes et al, 1983). Further studies are directed toward the assessment of eIF-2 phosphorylation state in vivo following ischemia to determine whether such a mechanism could account for the postischemic reduction in brain protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…For the purified aortic phosphatase, a Hill coefficient of 0-98-1-02 has been obtained (unpublished observation). In the turkey gizzard, two types of protein phosphatase have been isolated (Fato, Adelstein, Crouch, Safer, Ingebritsen & Cohen, 1983). Therefore, it is possible that the Hill coefficient of less than 1P0 may reflect the heterogeneity of the phosphatase activity in the taenia coli.…”
mentioning
confidence: 99%